2011
DOI: 10.1155/2011/101437
|View full text |Cite
|
Sign up to set email alerts
|

Design of Intelligent Self‐Tuning GA ANFIS Temperature Controller for Plastic Extrusion System

Abstract: This paper develops a GA ANFIS controller design method for temperature control in plastic extrusion system. Temperature control of plastic extrusion system suffers problems related to longer settling time, couple effects, large time constants, and undesirable overshoot. The system is generally nonlinear and the temperature of the plastic extrusion system may vary over a wide range of disturbances. The system is designed with three controllers. The proposed GA ANFIS controller is the most powerful approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 12 publications
0
18
0
3
Order By: Relevance
“…This merged technique of the learning power of the ANNs with the knowledge representation of FL has created a new hybrid technique, called neuro fuzzy networks or adaptive neuro fuzzy inference system (ANFIS) [14]. ANFIS, as a hybrid intelligent system that enhances the ability to automatically learn and adapt, was used by researchers for modeling [15,16], predictions [17][18][19] and control [20,21] in various engineering systems. The basic idea behind these neuro-adaptive learning techniques is to provide a method for the fuzzy modeling procedure to learn information about data [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This merged technique of the learning power of the ANNs with the knowledge representation of FL has created a new hybrid technique, called neuro fuzzy networks or adaptive neuro fuzzy inference system (ANFIS) [14]. ANFIS, as a hybrid intelligent system that enhances the ability to automatically learn and adapt, was used by researchers for modeling [15,16], predictions [17][18][19] and control [20,21] in various engineering systems. The basic idea behind these neuro-adaptive learning techniques is to provide a method for the fuzzy modeling procedure to learn information about data [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The three most significant variables were selected and applied to develop an ANFIS model. ANFIS is a robust tool favored by researchers for modeling (Al-Ghandoor and Samhouri 2009;Petković et al 2012a, b;Petković and Ćojbašić 2012), making predictions (Hosoz et al 2011;Gocić et al 2015b;Sivakumar and Balu 2010) and control in engineering systems (Kurnaz et al 2010;Ravi et al 2011;Khoshnevisan et al 2015;Petković et al 2012a, b;Tian and Collins 2005). ANFIS facilitates a fuzzy modeling procedure to gather data (Aldair and Wang 2011) and it can also be used to organize fuzzy inference systems using input/output data pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results showed that the optimised controller gave a much faster settling time with no overshoot. Ravi and Balakrishnan [36,37] used AI techniques in extruder barrel temperature control. The results showed that a FLC can perform well with a lesser overshoot than a PI controller.…”
Section: B Control Schemes Based On Artificial Intelligence Techniquesmentioning
confidence: 99%